2015
DOI: 10.5194/amt-8-1197-2015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the consistency among global microwave land surface emissivity products

Abstract: Abstract. The goal of this work is to intercompare four global land surface emissivity products over various landcover conditions to assess their consistency. The intercompared land emissivity products were generated over a 5-year period (2003)(2004)(2005)(2006)(2007) using observations from the Advanced Microwave Scanning Radiometer -Earth Observing System (AMSR-E), the Special Sensor Microwave Imager (SSM/I), the Tropical Rainfall Measuring Mission (TRMM) Microwave Imager (TMI), and WindSat. First, all produ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Evaluation of roughness effects by the Hr parameter (i.e., surface roughness) showed that some spatial patterns in the Hr values could be associated with the main vegetation types (higher values The vertically and horizontally polarized land surface emissivity at 10 GHz and the difference in polarization were consistent with the spatial variation in the land surface cover type on the Qinghai-Tibetan Plateau. Norouzi et al also found that emissivity values have frequency dependency over different land-cover types [48]. The northwest of the Qinghai-Tibetan Plateau is bare or semi-desert and the southeast is covered by shrubland, grassland, forest and other vegetation.…”
Section: Resultsmentioning
confidence: 97%
“…Evaluation of roughness effects by the Hr parameter (i.e., surface roughness) showed that some spatial patterns in the Hr values could be associated with the main vegetation types (higher values The vertically and horizontally polarized land surface emissivity at 10 GHz and the difference in polarization were consistent with the spatial variation in the land surface cover type on the Qinghai-Tibetan Plateau. Norouzi et al also found that emissivity values have frequency dependency over different land-cover types [48]. The northwest of the Qinghai-Tibetan Plateau is bare or semi-desert and the southeast is covered by shrubland, grassland, forest and other vegetation.…”
Section: Resultsmentioning
confidence: 97%
“…Since the different emissivity data sets can have considerable inconsistencies [Ferraro et al, 2013;Tian et al, 2013;Norouzi et al, 2015], it is necessary to emphasize that we are in fact testing the different methods' capability to reproduce a given reference, not the "truth." This is still meaningful for applications such as GPM's GPROF-based retrievals, since GPROF will use a retrieved emissivity data set to build its database, and it is more pertinent to produce good predictions relative to that data set instead to truth.…”
Section: Spatial and Temporal Domains And Datamentioning
confidence: 99%
“…The study found considerable differences not only between the modeled and retrieved emissivities but also among the retrieved emissivity values from different sensors or different data providers. Follow-up studies have been expended to include other surface types [Tian et al, 2013], more reliable retrieved emissivity retrievals [Ringerud et al, 2014], or broader spatial and temporal coverages [Norouzi et al, 2015;Prigent et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the factors controlling the natural variability of the MW land surface emissivity are a key focus of the National Aeronautics and Space Administration (NASA) Precipitation Measurement Missions (PMM) Land Surface Working Group (LSWG) (Ferraro et al ., ; Norouzi et al ., ; Tian et al ., ). Land surface modelling has demonstrated the complex relationships between physical surface emissivity factors such as soil composition, soil moisture and vegetation at GMI‐like frequencies (Ringerud et al ., ; Harrison et al, ).…”
Section: Introductionmentioning
confidence: 98%